The Effect of Integrated Prevention and Treatment on Child Malnutrition and Health in Mali: A Cluster Randomized Intervention Study (PROMIS-Mali) - Ruel, Marie T.; Rawat, Rahul; Savadogo, Abdoul Salam (International Food Policy Research Institute, 2015)
This project will address two critical gaps related to the integration of preventive and treatment programs: 1) screening and treatment of MAM/SAM have not yet been systematically integrated into routine health-center visits or mainstreamed into community outreach programs; and 2) screening programs do not offer any preventive services for those children found not to be suffering from MAM/SAM at the time of screening; mothers of children identified as non-MAM/SAM case are usually sent home without receiving any health or nutrition inputs and as a result, may fail to come back for screening because they do not see any tangible benefit associated with their participation in the screening. This project will specifically address these gaps by assessing the effect of an integrated approach consisting of higher screening coverage and preventive Behavior Change Communication (BCC) + Small-Quantity Lipid-based Nutrient supplementation (SQ-LNS) on both prevention and treatment of child undernutrition.